The Crab Mentality in Organisational Culture: An Analysis of Behavioural Dynamics and Their Impact - Dewa Ayu Made Mirah Annisa Chyntia Devi Annisa Chyntia Devi (Jurnal Pendidikan Rafflesia, 2026)
Crab mentality is a social behavior characterized by individuals’ tendency to hinder others’ success due to jealousy, feelings of inferiority, and unhealthy competition. Within community organizations, this behavior may weaken interpersonal communication, disrupt collaborative culture, and reduce collective performance effectiveness. This study aims to analyze the behavioral dynamics of crab mentality in organizational culture and its impacts on organizational communication, social perception, and group performance. The research employs a thematic literature review approach by examining scholarly articles, academic books, and previous studies in organizational communication, social psychology, and community management. Data were analyzed using narrative synthesis by categorizing findings into themes such as organizational communication, organizational culture, social perception, and manifestations of crab mentality. The findings indicate that limited communication openness, distorted social perceptions, and unsupportive organizational culture are key factors contributing to the emergence of crab mentality. This behavior manifests through gossip, cynical comments, covert sabotage, and lack of appreciation, resulting in decreased solidarity, increased conflicts, lower motivation, and organizational stagnation. Therefore, strengthening open communication, collaborative values, and psychological support is essential to minimize crab mentality and foster a healthy organizational culture.